On-ice performance characteristics of elite and non-elite women's ice hockey players - Bracko, M. R. (The Journal of Strength and Conditioning Research, 2001)
The purpose of this study was to compare skating performance and on-ice fitness of elite and non-elite women's ice hockey players. Twenty-three players who were participants in an organized women's hockey training program were tested. Seven of the elite players were members of the 1996/1997 Canadian National Team and 1 was from the Finnish National Team. Skating tests included (a) agility cornering S turn (AGL), (b) 6.10-m acceleration (ACC), (c) 47.85-m speed (SPD), (d) 15.20-m full speed (FSPD), and (e) Reed repeat sprint skate test (RRS). Elite players were older (25 ± 5.34 vs. 19 ± 2.65 years) and had better performance in the following variables: FSPD (1.88 ± 0.11 vs. 1.96 ± 0.86 seconds); RRS, drop-off percent (23.25 ± 5.85% vs. 34.98 ± 8.45%), drop-off time (3.43 ± 0.78 vs. 5.35 ± 1.23 seconds); of 6 repeats (101.96 ± 2.74 vs. 112.78 ± 4.61 seconds); and anaerobic capacity (AnCap; 5.35 ± 0.14 W·kg1 vs. 4.87 ± 0.19 W·kg1) as calculated by the formulas of Watson and Sargeant. These results suggest that elite women's ice hockey players are older, faster skaters; have a better drop-off percent, drop-off time, and of 6 repeats in a repeat skate test; and have greater on-ice anaerobic capacity than non-elite players.